Factors associated with the survival outcomes of patients with untreated hepatocellular carcinoma: An analysis of nationwide data - Kwon, Min Jung; Chang, Soy; Kim, Ji Hoon; Han, Ji Won; Jang, Jeong Won; Choi, Jong Young; Yoon, Seung Kew; Sung, Pil Soo (Frontiers in Oncology, 2023)
In this study, we examined the natural course of untreated hepatocellular carcinoma (HCC) in a hepatitis B virus-endemic area and identify predictors of survival. We identified 1,045 patients with HCC who did not receive HCC treatment and were registered in the Korean Primary Liver Cancer Registry between 2008 and 2014, with follow-up ending in December 2018. Thereafter, we analyzed the clinical characteristics of the patients who survived for <12 or ≥12 months. A Cox proportional regression model was used to identify the variables associated with patient survival. The mean age of the untreated patients at HCC diagnosis was 59.6 years, and 52.1% of them had hepatitis B. Most untreated patients (94.2%) died during the observation period. The median survival times for each Barcelona Clinic Liver Cancer (BCLC) stage were as follows: 31.0 months for stage 0/A (n = 123), 10.0 months for stage B (n = 96), 3.0 months for stage C (n = 599), and 1.0 month for stage D (n = 227). Multivariate Cox regression analysis demonstrated that BCLC stage D (hazard ratio, 4.282; P < 0.001), model for end-stage liver disease (MELD) score ≥10 (HR, 1.484; P < 0.001), and serum alpha-fetoprotein (AFP) level ≥1,000 ng/mL (HR, 1.506; P < 0.001) were associated with poor survival outcomes in patients with untreated HCC. In untreated HCC patients, advanced stage BCLC, serum AFP level ≥1,000 ng/mL, and MELD score ≥10 were significantly associated with overall survival.